Genetic manipulation of porcine deltacoronavirus reveals insights into NS6 and NS7 functions: a novel strategy for vaccine design - Mengjia Zhang; Wan Li; Peng Zhou; Dejian Liu; Rui Luo; Anan Jongkaewwattana; Qigai He (Emerging Microbes and Infections, 2020)
ABSTRACTPorcine deltacoronavirus (PDCoV) is an emerging swine coronavirus that causes severe diarrhea, resulting in high mortality in neonatal piglets. Despite widespread outbreaks in many countries, no effective PDCoV vaccines are currently available. Here, we generated, for the first time, a full-length infectious cDNA clone of PDCoV. We further manipulated the infectious clone by replacing the NS6 gene with a green fluorescent protein (GFP) to generate rPDCoV-ΔNS6-GFP; likewise, rPDCoV-ΔNS7 was constructed by removing the ATG start codons of the NS7 gene. Growth kinetics studies suggest that rPDCoV-ΔNS7 could replicate similarly to that of the wild-type PDCoV, whereas rPDCoV-ΔNS6-GFP exhibited a substantial reduction of viral titer in vitro and in vivo. Piglets inoculated with rPDCoV-ΔNS7 or wild-type PDCoV showed similar diarrheic scores and pathological injury. In contrast, rPDCoV-ΔNS6-GFP-infected piglets did not show any clinical signs, indicating that the NS6 protein is an important virulence factor of PDCoV and that the NS6-deficient mutant virus might be a promising live-attenuated vaccine candidate. Taken together, the reverse genetics platform described here not only provides more insights into the role of PDCoV accessory proteins in viral replication and pathogenesis, but also allows the development of novel vaccines against PDCoV infection.